2017
DOI: 10.15446/revfacmed.v65n4.60489
|View full text |Cite
|
Sign up to set email alerts
|

Publicación científica entre los directivos de la Asociación Científica de Estudiantes de Medicina de Colombia: características y factores asociados

Abstract: INVESTIGACIÓN ORIGINAL | Resumen |Introducción. La publicación científica se debe incentivar desde el pregrado, sobre todo en carreras de ciencias de la salud.Objetivo. Determinar las características y los factores asociados a la publicación científica entre los miembros de la Asociación Científica de Estudiantes de Medicina de Colombia (ASCEMCOL). Materiales y métodos.Se realizó un estudio transversal analítico que se basó en una encuesta presencial aplicada a los miembros de la ASCEMCOL. Se definió como publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…In addition, in our study, personal characteristics such as gender or civil status were not associated with scientific production, which coincides with what was reported with evidence. 25 , 26 It is important to mention that significant differences have been reported in terms of female and male scientific production, highlighting the low level of representativity of female scientists in the published articles. 27 This contrast could be due to the methodological or sample characteristics’ differences between the present study and the cited studies, although this found difference serves as the basis for questioning why there is still a low level of women’s scientific production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in our study, personal characteristics such as gender or civil status were not associated with scientific production, which coincides with what was reported with evidence. 25 , 26 It is important to mention that significant differences have been reported in terms of female and male scientific production, highlighting the low level of representativity of female scientists in the published articles. 27 This contrast could be due to the methodological or sample characteristics’ differences between the present study and the cited studies, although this found difference serves as the basis for questioning why there is still a low level of women’s scientific production.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we did not find an association between time working as a professor and scientific production, which is similar to what was reported by another study in 2018. 26 This could be due to the fact that probably professionals’ research practice is, in many cases, related to pre-professional training. Therefore, independently from the time a professional is practicing as a professor, it will be more complicated that they conduct research if they have not been motivated during their university education.…”
Section: Discussionmentioning
confidence: 99%
“…Frente a aspectos referidos a actores externos -como es el caso de las IES-, el estudio realizado por Pulido-Medina et al (2017), en una asociación de estudiantes de medicina, para la identificación de factores asociados a la intención de llevar a cabo publicaciones científicas demuestra, a diferencia del estudio aquí expuesto, que para la inmersión en actividades de alfabetización científica para los estudiantes sí es relevante el apoyo institucional. De hecho, los autores en su estudio muestran que la reducción del número de publicaciones de los estudiantes está vinculada con la percepción de apoyo de la universidad que éstos poseen.…”
Section: Discussionunclassified
“…Además, se agrupan principalmente en sociedades científicas para brindar capacitación en diversos temas relacionados con la investigación, a través de cursos, conferencias o asistencia a congresos y simposios científicos, lo que crea un motivo para la investigación científica y la publicación en la investigación universitaria. (32,33,34,35) Si bien los estudiantes están motivados para realizar investigación, son pocos los que llegan a presentar sus Salud, Ciencia y Tecnología. 2023; 3:562 2 trabajos a congresos o a publicarlos en revistas indizadas.…”
Section: Introductionunclassified